Pendampingan Pembelajaran Membaca AlQuran Menggunakan Metode Al Hidayah di SMP Al-Madinah Kabupaten Solok - Yafi, Salman; Kustati, Martin; Gusmirawati, Gusmirawati (Al-DYAS, 2023)
Learning to read the Qur'an often experiences obstacles due to the methods used that are not in accordance with the needs. The use of methods in learning to read the Qur'an should be tailored to the student's condition, both based on age and ability level. And also the use of the method depends on how the method is taught and the criteria of the teacher who teaches the method. The purpose of the activity of Learning to Read the Qur'an Using the Al Hidayah Method at Al-Madinah Junior High School is to facilitate students in learning to read the Qur'an. The methods used are mentoring and direct practice. In practice, the Al-Hidayah method uses emphasis by presenting color variations to make it easier for students to remember and practice directly the material taught. In addition, the Al-Hidayah Method also emphasizes the teacher's ability to recite the material taught. The method used in this assistance is the Participatory Action Research (PAR) approach which empowers students to make it easier to learn to read the Quran. The results obtained after these activities are that students find it easier to learn to read the Qur'an. Students are easier to read hijaiyah letters according to their makhraj. Students also easily understand other materials presented in the Al-Hidayah book as well as how to read the Qur'an properly and correctly.